Interpretasi Personal Branding Ian Hugen dalam Menyuarakan Citra Positif Transgender di Media Sosial Instagram - Daniel Dwi Fabian; Septia Winduwati (Kiwari, 2023)
Humans are social beings who live side by side and depend on one another. Humans live in groups and humans who live in groups in an area are called communities. However, there is a group of people who are not part of society. An example is the LGBT community, the LGBT community often gets treatment from society. The LGBT community is considered to have a negative stigma because it is against religious law. Because of this, the LGBT community often receives treatment in their environment and on social media. However, in the midst of the LGBT community, there is a transgender figure who has good personal branding. That figure was Ian Hugen. Ian Hugen is a public figure who is also a transgender person and Ian Hugen often insults self-love on social media so that he often receives praise from netizens. In this study the authors used the concepts/theories of communication, meaning, transgender, image, and social media. This study used qualitative research methods. The results of this study are informants on the meaning of Ian Hugen's personal branding in positive image deception which is dominated by the position of meaning. This is reinforced by the 8 elements of personal branding fulfilled by Ian Hugen. Manusia merupakan makhluk sosial yang hidup berdampingan dan bergantung satu sama lain. Manusia hidup secara berkelompok dan manusia yang hidup secara berkelompok pada suatu daerah disebut masyarakat. Akan tetapi, ada sekelompok manusia yang tidak menjadi bagian dari masyarakat. Komunitas LGBT kerap kali mendapatkan diskriminasi dari masyarakat. Komunitas LGBT dianggap memiliki stigma yang negatif karena berlawanan dengan hukum agama. Oleh karena itu, komunitas LGBT kerapkali mendapatkan diskriminasi dilingkungannya maupun di media sosial. Namun, ditengah-tengah komunitas LGBT, terdapat sosok transgender yang memiliki personal branding yang baik. Ian Hugen sebagai seorang public figure yang juga transgender dan sering kali menyuarakan tentang self-love di media sosial. Pada penelitian ini penulis menggunakan konsep/teori komunikasi, pemaknaan, transgender, citra, dan media sosial. Penelitian ini menggunakan metode penelitian kualitatif. Hasil penelitian ini menunjukkan bahwa Ian Hugen memenuhi delapan elemen personal branding menurut Montoya. Hal tersebut diperkuat dengan pemaknaan informan terhadap personal branding Ian Hugen dalam menyuarakan citra positif transgender melalui media sosial Instagram yang di dominasi dengan posisi pemaknaan Dominan.